Effects on welfare and poverty of the increase in international prices of agricultural commodities. A simulation exercise for Argentina, México and Uruguay - Barone, Sergio (2015)
Fil: Barone, Sergio. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.